2013
DOI: 10.3329/seajph.v2i2.15956
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with use of antenatal care services in a rural area of Bangladesh

Abstract: Antenatal care (ANC) includes care during pregnancy, should begin from the early stages of pregnancy. ANC allows management of pregnancy, detection and treatment of complications, and promotion of better maternal and child health. This study assessed the factors relating to maternal healthcare practices in rural Bangladesh and examined the association between use of antenatal care services and socio-demographic variables of rural women. A community based cross-sectional study was conducted in Madhupur upazila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 6 publications
(6 reference statements)
5
39
0
Order By: Relevance
“…Other factors such as age, total number of living children, wealth index and mode of transport were important that positively correlates the use of ANC during pregnancy of the postnatal. 3 Along with socioeconomic disparities, cost concern for medical treatment founded as principal reason for failing to seek care for life-threatening complications during pregnancy among Bangladeshi women. 8 Women reported low using of antenatal care as well as low rates of delivery with the assistance of a skilled provider and women who didn't seek effective treatment were those with the most severe life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors such as age, total number of living children, wealth index and mode of transport were important that positively correlates the use of ANC during pregnancy of the postnatal. 3 Along with socioeconomic disparities, cost concern for medical treatment founded as principal reason for failing to seek care for life-threatening complications during pregnancy among Bangladeshi women. 8 Women reported low using of antenatal care as well as low rates of delivery with the assistance of a skilled provider and women who didn't seek effective treatment were those with the most severe life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
“…These services can be taken either by visiting a health centre where such services are available or from health workers during their domiciliary visits. 3 Though Bangladesh has made a significant improvement towards achieving the Millennium Development Goal (MDG) target no. 5 on improving maternal health, pregnancy related complications remains the leading cause of death and disability among women who are in reproducible age.…”
mentioning
confidence: 99%
“…In a few studies, it was found that factors such as mother's age at birth, gender of child, wealth index, birth order, exposed to media etc. may play vital role in influencing ANC visit during pregnancy (Magadi et al 2000, Nisar and White 2003, Overbosch et al 2004, Sibley et al 2004, Sharma 2004, Alam et al 2005, Kabir et al 2005, Shahjahan et al 2012, Rahman et al 2017). An attempt has been made to identify whether maternal education influences ANC visit during pregnancy in Bangladesh using sequential logistic regression models.…”
Section: Introductionmentioning
confidence: 99%
“…5 According to the WHO recommendation, every pregnant woman should receive at least four antenatal care (ANC) visits during pregnancy. The use of ANC in developing countries is low compared to developed countries (97%) 4 due to the…”
mentioning
confidence: 99%
“…They constitute more than one-fifth of the world's population and are repeatedly exposed to the risk of pregnancy and childbearing. 4 Maternal health refers to the health of the mother during pregnancy, childbirth, and the postpartum period. The use of maternal healthcare services is important for the early detection of mothers who are at a high risk of morbidity and mortality during pregnancy.…”
mentioning
confidence: 99%